Advances in food and nutrition research . - Taylor, Steve L. (Elsevier, 2009)
Recognizes the integral relationship between the food and nutritional sciences. This book focuses on scientific developments in the broad areas of food science and nutrition. It is suitable for food scientists and nutritionists.